REHABILITATION PROGRAM FOR BELL'S PALSY PATIENTS - CASE REPORT - Ningsih, Dwy; Widodo, Agus; Kusumawati, Ana (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Bell's palsy is an idiopathic paralysis that affects more than half of the facial muscles due to injury at the bottom of the seventh cranial nerve, and symptoms of facial muscle weakness or total paralysis . Bell's palsy is an acute peripheral type VII nerve palsy whose cause is unknown. Bell's palsy is one of the most common problems affecting the motor neurons of the facial muscles both unilaterally and bilaterally. It affects function and quality of life. Therefore, physiotherapists focus on restoring facial function with different modalities as well as exercises. Case Presentation: Patients complain thick on the face of the left, unable to close his left eye completely, unable to lift his left eyebrow and lip merot right. On examination of the muscles there is a decrease in muscle strength on the side of the face. The diagnosis for this patient's case was Bell's palsy. Management and Outcome: Patients complain thick on the face of the left, unable to close his left eye completely, unable to lift his left eyebrow and lip merot right. Around 22:00 WIB on January 6, 2021, the patient felt half dizzy on the left side of his head and buzzing in his left ear. Because it is not strong enough to withstand the dizziness, the patient compresses with ice. In the morning when he woke up the patient felt a thick patch on the left side of his face. The patient looks in the mirror and notices changes in the face with drooping lips to the right Discussion: : Physical therapy is given to patients bell's palsy is to increase the strength of the facial muscles. The intervention given in this case is infrared to provide a relaxing effect and to increase metabolism, then electrical stimulation is given to stimulate weak muscles, massage is given with the aim of providing stimulation to the muscles which will later have the effect of increasing muscle strength, and the last is mirror exercise where this exercise is given to increase the functional activity of the patient. Conclusion: In the case of Bell's palsy, physiotherapy programs in the form of infrared, electrical stimulation, massage, and mirror exercises can increase muscle strength and increase functional activity in patients.